Prevalence of obesity and its related factors among Malay government employees in Kangar, Malaysia - Kalmi, Zahratul Nur (2012)
This is a cross-sectional study involving 272 randomly selected respondents (151 males and 121 females) from government agencies in Kangar, Perlis. Main objective of this study was to determine factors related to body weight status among government employees in Kangar Perlis. The data were collected by using self-administered questionnaires which have been translated to Bahasa Malaysia. Anthropometric measurements including weight, body fat percentage (BF%), height, waist circumference (WC) and blood pressure were assessed using Tanita body composition analyzer (Tanita TBF-306, Body Composition Analyzer, Japan), Body Meter (SECA 206, Body Meter, Germany), non-stretchable tape measure and digital blood pressure monitor (Omron HEM-780, Digital Blood Pressure Monitor, Japan). A 8-12 hour fasting venous blood sample was taken for analysis of plasma glucose, lipid profile and 2 hours oral glucose tolerance test (OGTT). All respondents were required to wear an accelerometer (Lifecorder e-Step, Suzuken Company Limited, Japan) for 3 days for physical activity level (PAL) assessment.There were more respondents with overweight body mass index (BMI) status (37.5%) than normal BMI (34.9%) and among overweight respondents, there were more male (42.4%) than female respondents (31.4%). For PAL, most of the respondents were categorized under moderate level of PA (47.7% of male and 66.9% of female) by using IPAQ, and only 22.1% and 21.7% were categorized in low and high level PA. For accelerometer-determined of PAL, most of the respondents were classified as sedentary (55.1%) and only 8.0% were classified under vigorous PAL. On the other hand, when steps per day were used as PAL measure, most of the respondents (62.1%) were classified as inactive and there were only 15.4% and 7.7% of the respondents were categorized into sedentary and active level. For fasting plasma glucose level, there were more male respondents categorized as having impaired fasting plasma glucose and required provisional diagnosis compared to female respondents (18.0% and 10.7%). There were 14.8% having impaired 2Hr plasma glucose and needed provisional diagnosis. In term of total cholesterol, triglyceride and LDLC level, although most of the respondents were categorized as having normal level, more male respondents were categorized in high level (23.8%, 29.5% and 39.3%) compared to female respondents (12.6%, 5.8% and 18.4%). For HDLC level, there were only 2.2% of the respondents with high level HDLC which was good for health. Most of the respondents (81.6%) were normal in term of eating behavior and there were only 18.4% of the respondents who were at risk of having eating disorder, with female respondents (23.1%) had higher percentage of having eating disorder compared to male respondents (14.6%).For multiple linear regressions, there were three models developed in the study to predict BMI (Model 1), WC (Model 2) and BF% (Model 3). It showed that in addition to the accelerometer- determined PAL, diastolic blood pressure, stages of change in body weight management, age and triglyceride were also significant predictors of BMI of the respondents, while age, sex, diastolic blood pressure, stages of change in body weight management and triglyceride were the other significant predictors of WC of the respondents. On the other hand, BF% was significantly predicted by accelerometer-determined PAL, diastolic blood pressure, stages of change in body weight management, IPAQ and systolic blood pressure. The explained variance in each regression models was significant. All the three models showed that PAL made the strongest significant contribution in predicting the dependent variable in each model. Diastolic blood pressure and stages of change in body weight management also shows significant contribution in all the three models. On the other hand, age and triglycerides were significant contributors for BMI and WC, but not for BF%. In addition, sex made significant contribution for WC alone, while PAL determined by IPAQ and systolic blood pressure only made significant contribution to BF%. This study suggested that accelerometer-determined PAL made the strongest unique contribution in explaining body weight status, followed by diastolic blood pressure and stages of change in body weight management.